Estimasi Biaya Perangkat Lunak SIMAS Universitas XYZ Menggunakan Metode Function Points - Lovita Lisa Nur Afifah; Setya Suprayogi; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2019)
Accurate cost estimation in developing a software is very important to avoid over-estimating or under-estimating. The estimation method used is using the Function Points method. The stages of the Function Points method are the first step to compose 5 main parameters and calculate the total UCP, the second step to calculate the total RCAF by referring to 14 characteristics, the third step to calculate the Function Point, the fourth step to calculate the effort, the fifth step to calculate SLoC, the sixth step to calculate SLoC to effort and seventh counts the distribution of effort to activity. From the research that has been done, the estimated cost of developing SIMAS XYZ University software, it is concluded that if XYZ universities want to develop SIMAS software, it will require approximately IDR77,736,766 or equivalent to effort 1,520.74 man / hour.